OVERVIEW STUDI KELAYAKAN BISNIS - Mairani Adelia; M. Abiyyu Wadi; Suci Haryanti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
A Business Feasibility Study is a vital element in the planning and development of a new venture, aiming to evaluate a business idea's potential success and feasibility before its implementation. This article discusses the importance of a business feasibility study, describing an evaluation process that involves economic, technical, legal, market and financial aspects. By conducting a thorough feasibility study, entrepreneurs can identify risks, minimize losses, and ensure efficient use of resources. The article also highlights the various stages in a feasibility study, from idea implementation to execution, as well as the necessary primary and secondary data sources for the analysis of the operational, industrial, and remote environments. Findings show that a comprehensive business feasibility study is an essential foundation for planning and running a business successfully, as well as providing strategic guidance for better decision-making.